2018
DOI: 10.3390/nano8080605
|View full text |Cite
|
Sign up to set email alerts
|

Hexagonal Boron Nitride Functionalized with Au Nanoparticles—Properties and Potential Biological Applications

Abstract: Hexagonal boron nitride is often referred to as white graphene. This is a 2D layered material, with a structure similar to graphene. It has gained many applications in cosmetics, dental cements, ceramics etc. Hexagonal boron nitride is also used in medicine, as a drug carrier similar as graphene or graphene oxide. Here we report that this material can be exfoliated in two steps: chemical treatment (via modified Hummers method) followed by the sonication treatment. Afterwards, the surface of the obtained materi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
45
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 70 publications
0
45
0
Order By: Relevance
“…The optimization to use two-step exfoliation technique combining chemical and mechanical exfoliation was also reported [29]. Chemical exfoliation of h-BN was carried out by a modified Hummer's method.…”
Section: Synthesis Methods Of Few-layered H-bn (Fbn)mentioning
confidence: 99%
See 4 more Smart Citations
“…The optimization to use two-step exfoliation technique combining chemical and mechanical exfoliation was also reported [29]. Chemical exfoliation of h-BN was carried out by a modified Hummer's method.…”
Section: Synthesis Methods Of Few-layered H-bn (Fbn)mentioning
confidence: 99%
“…In research [29] simple and repeatable Au-fBN nanocomposite synthesis method was demonstrated. Briefly, exfoliated h-BN was sonicated in distilled water.…”
Section: Functionalization Of Few-layered H-bn (Fbn)mentioning
confidence: 99%
See 3 more Smart Citations